Undergraduate Students’ Marriage: (A Case Study Of Problematics Of College Students Who Get Merried During Their Study) (Jurnal Bimbingan dan Konseling Islam, 2020)
The aims of this research were (1) to get the information of underlying factors of college students’ marriage during their studies, (2) to find out the exact problems of college students’ marriage during their studies, and (3) to find out the ways to solve the problems of college students’ marriage during their studies. This research was a qualitative research using a case study research design. The main units of analysis were three pairs of respondents and their parents and friends. The data were gained by means of observation, documentation, and interview. The validity of data was obtained through triangulation technique and triangulation source. Data analysis techniques were conducted by adopting interactive model Miles & Huberman. The results showed: (1) Underlying factors of marriage included a) internal factors such as love and knowledge of religion, b) external factors such as encouragement from parents, unwed pregnancy, economic factors, and social and cultural circumstances. (2) Problems faced by married college students during their study were. a) academic problems, that is often do not go to college, laziness and bad time management, b) non-academic problems such as their monotonous and selfish personality and polygamy case as well. (3) The solution of college students’ marriage problems was time management, college leave, dialogue to solve the problems, consultation with religious figures and motivation.